(untitled) - Wong, John (Singapore, 1993)
This transition, which took place in a chaotic manner in Eastern Europe and the USSR during the 1990s, proceeded in a much more gradual process in China, in the context of strong economic growth and under the total control of the one-party system. In fact the Chinese bureaucracy drew some lessons from the experience of the USSR and it had already started introducing elements of a market economy before the collapse of the Berlin wall.
Keywords: Tiếp thị,Marketing; Trung Quốc,China